A ‘Split-Gene’ Transketolase From the Hyper-Thermophilic Bacterium Carboxydothermus hydrogenoformans: Structure and Biochemical Characterization - James, Paul; Isupov, Michail N.; De Rose, Simone Antonio; Sayer, Christopher; Cole, Isobel S.; Littlechild, Jennifer A. (Frontiers in Microbiology, 2020)
A novel transketolase has been reconstituted from two separate polypeptide chains encoded by a ‘split-gene’ identified in the genome of the hyperthermophilic bacterium, Carboxydothermus hydrogenoformans. The reconstituted active α2β2 tetrameric enzyme has been biochemically characterized and its activity has been determined using a range of aldehydes including glycolaldehyde, phenylacetaldehyde and cyclohexanecarboxaldehyde as the ketol acceptor and hydroxypyruvate as the donor. This reaction proceeds to near 100% completion due to the release of the product carbon dioxide and can be used for the synthesis of a range of sugars of interest to the pharmaceutical industry. This novel reconstituted transketolase is thermally stable with no loss of activity after incubation for 1 h at 70°C and is stable after 1 h incubation with 50% of the organic solvents methanol, ethanol, isopropanol, DMSO, acetonitrile and acetone. The X-ray structure of the holo reconstituted α2β2 tetrameric transketolase has been determined to 1.4 Å resolution. In addition, the structure of an inactive tetrameric β4 protein has been determined to 1.9 Å resolution. The structure of the active reconstituted α2β2 enzyme has been compared to the structures of related enzymes; the E1 component of the pyruvate dehydrogenase complex and D-xylulose-5-phosphate synthase, in an attempt to rationalize differences in structure and substrate specificity between these enzymes. This is the first example of a reconstituted ‘split-gene’ transketolase to be biochemically and structurally characterized allowing its potential for industrial biocatalysis to be evaluated.